Sowing in tears: a Christian response to HIV/AIDS of the Diocese of Tzaneen, South Africa - Servais, Norman; Slattery, Hugh; Begwa, David (Metanoia Media, 2007)
This film documents the response of the Diocese of Tzaneen, Limpopo Province, South Africa, to the HIV/AIDS pandemic in the region. They have adopted a three-pronged approach to fighting the disease: the Education for Life programme, home-based care and the care of orphans and needy children. Bishop Hugh Slattery, the Bishop of Tzaneen, speaks about the Diocese's concern for future generations.